A thermodynamic Equilibrium model of Fluidized bed Gasifier using ASPEN HYSYS - Ugwuodo, C.B; Ugwuoke, E.C; Owabor, C.N; Ogbeide, S.E (International journal of Engineering, Business and Management, 2020)
A steady state thermodynamic equilibrium model for biomass gasification in atmospheric fluidized bed gasifier was developed using Aspen Hysys version 10. The model addressed the physical properties of the oil palm frond (OPF) and the chemical reaction involved in the process. This chemical reactions is embedded in sequential set of reactors: conversion and equilibrium reactors. Oil palm frond (OPF) decomposition into constituents in the pyrolysis zone is modeled with a pyrolytic yield reactor. The combustion of char and volatiles in the combustion zone were modeled with a conversion and equilibrium reactor respectively. The gasification zone was also modeled with conversion and equilibrium reactor. The models of the gasification process were validated with both experimental data and simulation results from literature. The optimal condition of the process operating parameter like gasification temperature, steam-biomass ration and air-fuel ratio where found to influence the syngas compositions. Increase in temperature increases the hydrogen and carbon- monoxide composition in the syngas. The optimum temperature in the various zones of the gasifier: drying, pyrolysis, and volatile combustion where 300, 500 and 850 respectively and gasification temperature at the three gasifiers(A, B and C) are 940, 207 and 653 respectively. The steam to biomass ratio of 1.11 and air to fuel ratio of 0.104 were the optimal gasification condition. Steam to biomass increase favours the production of H_2 and 〖CO〗_2, which also increases the heating value of the synthesis gas.